From Cost-Benefit to Institutional Analysis in The Economics of the Environment - Lenka Slavikova (Contemporary Economics, 2013)
Economics of the environment as an applied field of economics was established during the 1960s. At the time of its foundation, neoclassical environmental economics represented the mainstream view regarding the explanation of the causes of environmental problems and their solutions. Since then, however, two other competing approaches - the free market and institutional ecological economics - have evolved. These two new approaches present different analytical focuses as they stress the role of institutions (property rights and/or management regimes) in environmental protection. As a result, environmental research based on cost-benefit analysis was substituted by the application of various forms of institutional (often qualitative) analyses. The goal of the paper is to justify the importance of this methodological shift that is sometimes minimized by mainstream economists. The research focus of competing approaches and their methods are mapped through comparative analysis, and the theoretical description is connected with the practical examples of the EU environmental policy.
Keywords: Q50; B25; 330; institutional analysis; environmental economics; qualitative research; interdisciplinarity